Real-time measurement of fill volume in a vessel using optical and acoustical means : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Engineering at Massey University, Manawatū, New Zealand. EMBARGOED until further notice. - Barzegar, Mohammad Amin (Massey University, 2024)
This thesis investigates optical and acoustical methods for quickly determining the fill volume in cavities, vessels, or hoppers. The motivation for this study was the demand in the New Zealand aerial topdressing industry for a system that can accurately track the fill volume of vessels containing powders. A notable challenge in this industry is that topdressing aircraft lack systems for measuring the volume of discharge vessels during flight, leading to issues with flight safety and operational efficiency. This thesis specifically addresses the challenge of real-time fill volume determination in hoppers within New Zealand's aerial topdressing industry. Additionally, the outcomes of this thesis may offer insights and applicable methods for other industrial and scientific sectors that require real-time, contactless volume determination techniques. Three contactless volume measurement approaches were investigated: ultrasonic range-finding, 3D scanning, and acoustical resonance. The first approach used an array of ultrasonic rangefinders installed in a 200-litre powder-containing vessel, resulting in material level readings from multiple points. This technique was tested under discharge and no-flow conditions. According to the results, this method provided readings of the vessel fill volume with a measurement rate of ~1 Hz and an uncertainty of ~3% of the vessel capacity. The second approach used stereoscopic technique to provide real-time scans of the material surface in the vessel. A model was developed for calculating the volume of material in the vessel using the vessel internal scans. According to the test results on different bulk materials under discharge and no flow conditions for two vessels of sizes 50 and 200 litres, the real-time fill volume of the vessel was obtained with uncertainties less than 1% of the vessel’s volume. The third approach explored Helmholtz Resonance for determining the volume of powders and solids. This involved studying the impact of inserting a sample into Helmholtz Resonators on resonance parameters. Three models were developed for volume estimation: an extended Helmholtz Resonance model modifying the classical equation for resonators with long ports, a model for estimating solid volume in powders based on resonance frequency and quality factor, and a model for instantaneous volume measurement of a vessel's empty cavity using Helmholtz Resonance. The latter correlated the change in cavity sound pressure to its volume, showing it could accurately determine volume in real-time with less than 0.1% error relative to the vessel capacity.
Listed in 2024 Dean's List of Exceptional Theses
Embargoed until further notice
Keywords: Volume (Cubic content); Measurement; Mathematical models; Measuring instruments; Resonators; Aerial fertilizing; acoustical measurement; volume measurement; volumetry; Helmholtz resonance; ultrasonics; stereoscopic instrumentation; hopper; topdressing; Dean's List of Exceptional Theses; 400906 Electronic sensors